Psychological Well-being in Adults with and without Asthma - Sadiq, Riffat; Javed, Huma; Jabeen, Hifza; Khan, Urwah; Fareed, Fizza; Ali, Fariha Ashiq; Sakhawat, Kainat; Tariq, Amna; Umar, Aneeta (Journal of Pakistan Psychiatric Society, 2021)
ObjectivesThe present study analyzed the psychological well-being of adults diagnosed with asthma in comparison to adults without asthma. It was postulated that adults with and without asthma will significantly differ in respect to psychological well-being (autonomy, environmental mastery, personal growth, positive relation with others, purpose in life and self-acceptance). MethodologyThe present comparative research was carried out over the period of six months. Total 120 participants were recruited for the present purpose including sixty (n = 60) adults diagnosed with asthma and sixty (n=60) without asthma. Data collection was done using demographic information form and Psychological Well-being Scale (42-items). Data was analyzed by computing independent samples t-test through SPSS Version, 22.0. ResultsStatistical analysis depicted a significant difference among adults with and without asthma in respected to in relation to environmental mastery (t = -3.59, df = 118, p = 0.000), personal growth (t = -4.40, df= 118, p =  .000), positive relations with others (t = -2.59, df = 118 , p = .011 ), purpose in life ( (t = -5.46 , df = 118, p = .000 ),  self-acceptance (t =  -2.26 , df = 118, p = 0.025 ) and psychological well-being (t = - 4.932, df = 118, p = 0.000). A non-significant difference was found out among adults on the variable of autonomy (t = -1.42, df = 118, p = 0.156).ConclusionPsychological well-being of adults is significantly influenced by asthma in terms of environmental mastery, personal growth, positive relations with others, purpose in life and self-acceptance.